Whole‐cell Escherichia coli lactate biosensor for monitoring mammalian cell cultures during biopharmaceutical production. Issue 6 (23rd February 2017) - Goers, Lisa; Ainsworth, Catherine; Goey, Cher Hui; Kontoravdi, Cleo; Freemont, Paul S.; Polizzi, Karen M.
ABSTRACT: Many high‐value added recombinant proteins, such as therapeutic glycoproteins, are produced using mammalian cell cultures. In order to optimize the productivity of these cultures it is important to monitor cellular metabolism, for example the utilization of nutrients and the accumulation of metabolic waste products. One metabolic waste product of interest is lactic acid (lactate), overaccumulation of which can decrease cellular growth and protein production. Current methods for the detection of lactate are limited in terms of cost, sensitivity, and robustness. Therefore, we developed a whole‐cell Escherichia coli lactate biosensor based on the lldPRD operon and successfully used it to monitor lactate concentration in mammalian cell cultures. Using real samples and analytical validation we demonstrate that our biosensor can be used for absolute quantification of metabolites in complex samples with high accuracy, sensitivity, and robustness. Importantly, our whole‐cell biosensor was able to detect lactate at concentrations more than two orders of magnitude lower than the industry standard method, making it useful for monitoring lactate concentrations in early phase culture. Given the importance of lactate in a variety of both industrial and clinical contexts we anticipate that our whole‐cell biosensor can be used to address a range of interesting biological questions. It also serves as a blueprint for how to capitalize on the wealth of genetic operons for metabolite sensing available in nature for the development of other whole‐cell biosensors. Biotechnol. Bioeng. 2017;114: 1290–1300. © 2017 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : Nature has evolved highly sensitive genetic detection elements that can be exploited to create low‐cost whole‐cell biosensors (WCB). Using lactate as an example, we show that it is possible to use WCB not just for detection, but also for quantification of concentration in complex samples such as mammalian cell culture media with a high degree of accuracy and greater sensitivity than the industry standard method. The results pave the way for the application of WCB in industrial bioprocess development.